Discovery of small molecule therapeutics for the Middle Eastern respiratory syndrome-coronavirus (MERS-CoV) - Gan, Jonathan Hanjie (Nanyang Technological University, 2020)
Middle-Eastern Respiratory Syndrome (MERS) is a coronavirus infection which affects the lower respiratory tract of infected individuals. Its high mortality rate of 34.5% led MERS to be listed as a high priority disease for research by the World Health Organisation (WHO). MERS can be both symptomatic and asymptomatic, which leads to a high rate of misdiagnosis and treatment. MERS-coronavirus (MERS-CoV) was identified as a beta-coronavirus in 2013, like Severe Acute Respiratory Syndrome-coronavirus (SARS-CoV) which resulted in a global outbreak in 2003. As there are currently no specific vaccines and therapeutics for this viral infection, there is an unmet medical need to develop drugs against MERS-CoV infection. To achieve this objective, three approaches were attempted: 1) Drug repurposing via structure-guided screening of FDA-approved drugs; 2) New fragment library screening; and lastly 3) Designing of peptide mimetics targeting MERS-CoV Receptor Binding Domain (RBD). Those attempts allowed us to identify a promising drug candidate, Montelukast Sodium Hydrate (MSH), which was previously used in the treatment of acute allergic rhinitis and asthma. Structural model predicted that MSH is engaged in the binding interface between MERS-CoV RBD and human DPP4 and consequently exerts inhibitory effects. The molecular basis of MSH in MERS-CoV infection has been studied while its potential clinical implications are discussed. Finally, validation studies on this potential therapeutic candidate were performed by employing live MERS-CoV. The results presented in this thesis provide insights into repositioning potential of existing drugs and an opportunity to design novel class of drugs to combat MERS-CoV infection.